2020
DOI: 10.1200/po.20.00021
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Fast-Progression, Hyperprogressive Disease, and Early Deaths in Advanced Non–Small-Cell Lung Cancer Treated With PD-1/PD-L1 Inhibitors or Chemotherapy

Abstract: PURPOSE Hyperprogressive disease (HPD), fast progression (FP), and early death (ED) have been described in 13.8%, 4.7%, and 5.6% and in 5.1%, 2.8%, and 6.8%, respectively, of patients with non–small-cell lung cancer (NSCLC) treated with single-agent programmed cell death ligand 1 inhibitors (ICI) or chemotherapy, respectively. Whether FP/ED and HPD represent overlapping patterns is unknown. PATIENTS AND METHODS FP, ED, and HPD were retrospectively assessed in patients with NSCLC treated with single-agent ICI o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 22 publications
1
14
0
Order By: Relevance
“…Among potential clinical criteria, we decided to include patients experiencing death within 12 weeks from the start of ICIs, being an objective criterion and a phenomenon already observed in several clinical trials [6,11]. Evidence about lack of complete overlap between the two phenomena, ED and HPD, in line with previous observations [23,24], has been confirmed in our experience. We also confirmed the potential impact of extrathoracic disease on the risk of developing ED or HPD and the occurrence of ED even in patients expressing high level of PD-L1 and treated in a first-line setting [3,10,25].…”
Section: Discussionsupporting
confidence: 57%
“…Among potential clinical criteria, we decided to include patients experiencing death within 12 weeks from the start of ICIs, being an objective criterion and a phenomenon already observed in several clinical trials [6,11]. Evidence about lack of complete overlap between the two phenomena, ED and HPD, in line with previous observations [23,24], has been confirmed in our experience. We also confirmed the potential impact of extrathoracic disease on the risk of developing ED or HPD and the occurrence of ED even in patients expressing high level of PD-L1 and treated in a first-line setting [3,10,25].…”
Section: Discussionsupporting
confidence: 57%
“…Biomarkers to predict these aggressive patterns are currently a major need for patients on ICI therapy. While, in lung cancer, high-dNLR at baseline was not initially associated with HPD [33], Kim et al recently reported that high-dNLR (>4) was independently associated with HPD (differently defined). We observed, using dNLR score, that 12-week death rate was higher in high-dNLR (B) population (27% vs. 15% overall), and increased up to 32% if continued high-dNLR, supporting the biological hypothesis of neutrophil involvement on ICI resistance [12].…”
Section: Discussionmentioning
confidence: 96%
“…Hyperprogressive disease (HPD) refers to cases that the volume of the tumor lesion does not decrease but increases after immunotherapy, with a faster disease progression (typically at least two times) compared to before treatment [133,134]. HPD induced by PD-1 inhibitor immunotherapy is another challenge for immunotherapy alone in addition to their low response rate.…”
Section: Stie and Time In Hyperprogressive Disease Following Pd-1 Inh...mentioning
confidence: 99%